Association between insulin resistance and post-ischaemic stroke outcome in patients without diabetes: protocol for a systematic review and meta-analysis. Issue 3 (26th March 2021) - Hadwen, Jeremiah; Kim, Woojin; Dewar, Brian; Ramsay, Tim; Davis, Alexandra; Dowlatshahi, Dar; Shamy, Michel
Abstract : Introduction: Insulin resistance is an independent risk factor for atherosclerosis, coronary artery disease and ischaemic stroke. Currently, insulin resistance is not usually included in post-stroke risk stratification. This systematic review and meta-analysis intends to determine if available scientific knowledge supports an association between insulin resistance and post-stroke outcomes in patients without diabetes. Methods and analysis: The authors will conduct a literature search in Medline, Embase, Web of Science and Cochrane Central. The review will include studies that assess the association between elevated insulin homeostasis model of insulin resistance (HOMA-IR) and post-stroke outcome (functional outcome and recurrent stroke). The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) reporting guidelines will be used. The primary outcome will be post-stroke functional outcome (Modified Rankin Scale), and the secondary outcome will be recurrent ischaemic stroke. Comparison of outcome will be made between highest and lowest HOMA-IR range (as defined in each article included in this systematic review). Risk of bias will be assessed qualitatively. Meta-analysis will be performed if sufficient homogeneity exists between studies. Heterogeneity of outcomes will be assessed by I ². Ethics and dissemination: No human or animal subjects or samples were/will be used. The results will be published in a peer-reviewed journal, and will be disseminated at local and international neurology conferences. PROSPERO registration number: CRD42020173608.